Pengaruh Perbedaan Rasio antara Sisa Pakan dan Feses Kambing Peranakan Etawah terhadap Kadar Unsur Hara Kompos - Sarastuti, Yanuarizky Hetty (2020)
The study purpose to evaluate the effect of different ratio of remain feed and manure of Etawah Crossed Bred goat on the chemical content of compost. In this study the ratio of remain feed and manure was 0:100 (T1), 30:70 (T2), 40:60 (T3) and 50:50 (T4). Material in each treatment was added with limestone, ash and inoculant. Compost was processed by piling material to make a heap. There were 3 heaps for each treatment. The heap of material was turned every 2 days. The process was considered complete when the temperature of material was similar to air temperature. During the study we collected data pertaining to process (temperature and pH) and chemical content of compost (dry matter, organic matter, carbon, nitrogen, phosphor and potassium). The result showed that the duration of process was 29 to 39 days. There was no significant effect of treatment on the temperature and pH during composting process. Temperature was 39.1 to 44.3 oC while pH was 7.3 to 7.6. The content of dry matter, phosphor and potassium of compost T1 was lower than those in compost T2, T3 and T4 but organic matter and nitrogen content were higher (P<0.05). Dry matter compost T1 was 33.1%, while T2, T3 and T4 were respectively 37.6%; 35.3% and 36.2%. Organic matter and nitrogen content of compost T1 were 24.5% and 1.2% , while those in T2, T3 and T4 respectively were 19.3% and 1.0%; 16.8% and 0.8%, 19.7% and 0.6%. Compost T4 (50:50) produced the highest C/N.The result showed that different of ratio between remains feed and goat manure did not affect the duration and condition of composting process. Based on the dry matter and organic matter content, compost T1 (100% manure) was better tahn T2, T3 and T4.